»Kdor ima to pismo s sabo …« Opombe k »hišnemu in varovalnemu pismu« - Ficker, Friedbert (Traditiones, 2007)
<span style="line-height: 115%; font-family: 'Helvetica','sans-serif'; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Focusing on a minor element of folk beliefs and superstitions, the article examines the belief, widespread at least until the First World War, that some objects and acts possess magical powers. The author suggests that folk beliefs in the magical power of certain objects have been saturated with Christian faith. The same holds true for supplications and letters of gratitude. Broaching a variety of subjects, most of which relate to the hardships of life, these letters address Virgin Mary, Jesus Christ, and saints. Contents of the so-called letters from heaven, household blessings, and letters of protection, all of which were documented as early as the end of the 15th and the beginning of the 16th century, has been ascribed to the Sacred that protects people from harm in their homes, on the road, and during wartime. One of these letters, bearing an inscription „Household Blessing and Protection Letter“, has been found by the author in his father‘s legacy. According to oral data, and in view of the fact that the letter was frayed and quite worn out, his father had been carrying it with him throughout the Second World War. Its wording indicates a model after which the letter was worded, possibly the Holstein type from the 18th century that was designed for use during wartime. <span style="line-height: 115%; font-family: 'Helvetica','sans-serif'; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">*** <span style="line-height: 115%; font-family: 'Helvetica','sans-serif'; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Članek obravnava drobnejšo temo iz ljudskega verovanja oz. praznoverja. Gre za nekdaj (vsaj do 1. svetovne vojne) precej razširjeno prepričanje o čarovni moči predmetov in dejanj. Avtor ugotavlja, da je ljudsko prepričanje v čarno moč predmetov zelo prežeto s krščansko vero, tako tudi v priprošnjih in zahvalnih pismih z izjemno raznovrstno vsebino, ki se večinoma nanaša na tegobe vsakdanjega življenja, nagovarjajo Marijo, Jezusa in svetnike. V t. i. nebeških, hišnih in varovalnih pismih, dokumentiranih že na koncu 15. in začetku 16. stoletja, pa je vsebina pripisana Svetemu, ki varuje posameznike doma, na poti, v vojni. Takšno pismo, z napisom »Hišno in varovalno pismo« je avtor našel tudi v zapuščini svojega očeta; po pripovedovanju in obrabljenosti sodeč ga je oče imel pri sebi skoz vso drugo svetovno vojno. Besedilo kaže na mogočo predlogo, tj. holsteinski tip iz 18. stoletja, namenjen rabi v vojnih časih.